Dynamic property investigation of segmented acoustic black hole beam with different power-law thicknesses. (19th March 2021) - Fu, Qidi; Du, Xiaofei; Wu, Jianwei; Zhang, Jianrun
Abstract: Traditional acoustic black hole (ABH) structure that usually has a wedge-shaped structure with unchanged power-law profile has been studied extensively. Embedding an ABH in a thin-walled structure can help the system to control the flexural wave to realize vibration damping and energy concentration. However, due to the limitations of processing and manufacturing technology, the structural thickness of the ABH region cannot completely reach zero and will always leave a truncation at the tip of the ABH region, which makes ABH structure cannot give full play to the effect of ABH. In this paper, we show that a beam with segmented ABH structure whose baseline is segmented into two portions and they are respectively subjected to different power functions can effectively improve the effect of ABH. A semi-analytical method is adopted to establish the dynamical model of the segmented ABH beam under the clamped-free boundary condition. Finite element method and experimental method are carried out to verify the accuracy of the semi-analytical model. The segmented ABH effect of the beam is analyzed by the comparison of segmented ABH beam, conventional ABH beam, and uniform beam. In addition, the influence of the damping layer location on the dynamic response of the segmented ABH beam is studied as well. The numerical simulation results show that the vibration energy of segmented ABH beam can be more effectively shifted to the ABH area, thus enhancing the energy concentration effect and vibration attenuation. Moreover, the results also reveal that attaching the damping layer to the tip of the segmented ABH structure can effectively improve the system modal loss factor and achieve better vibration attenuation. The research of this paper can give rise to explorations of different innovative ABH structures and broaden the application of ABH beam structures in engineering.